2007
DOI: 10.1242/jcs.013771
|View full text |Cite
|
Sign up to set email alerts
|

Mechanistic insights from structural studies of β-catenin and its binding partners

Abstract: β-catenin is both a crucial regulator of cell adhesion and the central effector of the canonical Wnt signaling pathway. It functions as a protein organizer by interacting with numerous partners at the membrane, in the cytosol, and in the nucleus. Recent structural and biochemical studies have revealed how β-catenin engages in critical protein-protein interactions by using its armadillo repeat region and its N- and C-terminal domains. The groove in the armadillo repeat region is a particularly interesting featu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
220
0
5

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 226 publications
(229 citation statements)
references
References 88 publications
(55 reference statements)
4
220
0
5
Order By: Relevance
“…It was previously shown that Vac8p interacts with Vac17p and Atg13p, and these interactions play essential roles in vacuole inheritance and the CVT pathway, respectively (13,14). Additionally, β-catenin, a structural homolog of Vac8p, shares the typical inner groove formed from the ARM repeats that serves as an interacting platform for their various binding partners (19). We therefore wondered whether Vac8p would also share Nvj1p-binding regions with Vac17p or Atg13p proteins.…”
Section: Resultsmentioning
confidence: 99%
“…It was previously shown that Vac8p interacts with Vac17p and Atg13p, and these interactions play essential roles in vacuole inheritance and the CVT pathway, respectively (13,14). Additionally, β-catenin, a structural homolog of Vac8p, shares the typical inner groove formed from the ARM repeats that serves as an interacting platform for their various binding partners (19). We therefore wondered whether Vac8p would also share Nvj1p-binding regions with Vac17p or Atg13p proteins.…”
Section: Resultsmentioning
confidence: 99%
“…This latter effect was primarily dependent on ␤-catenin binding to TCF4 and not to other possible-binding partners (49) because expression of dnTCF4 virtually negated the FGF9-mediated induction of HD5 mRNA expression. These results are consistent with prior studies showing that the canonical Wnt pathway regulates Paneth cell differentiation and, possibly, specification of the Paneth cell lineage in the intestine through Wnt/Frizzled-5 signaling and through regulation of Sox9, an HMG-box transcription factor expressed in intestinal crypt cells, including Paneth cells (10 -12).…”
Section: Discussionmentioning
confidence: 95%
“…Recently, the biological function of some classical arm repeat proteins have been well clarified. Such as β-catenin , a classical member of ARM family plays important roles both at cells adherence junctions and in Wnt signaling through interaction with E-cadherin and T cell factor/lymphoid enhancer factor (TCF/LEF) family transcription factors (Xu et al, 2007;Bass-Zubek et al, 2009). Tumor suppressor adenomatous polyposis coli (APC) is also an ARM family member and acts with casein kinase Ι, glycogen synthase kinase-3β and AXIN to regulate Wnt signaling through β-catenin degradation (Munemitsu et al, 1995; Rubinfeld et al, 1996; Goss et al, 2000), APC promoter methylation was found to be significantly associated with a higher risk of developing CRC and the findings indicate that APC promoter methylation may be a potential biomarker for the carcinogenesis of CRC (Ding et al, 2015).…”
Section: Discussionmentioning
confidence: 99%